Ekologia w programach nauczania religii dla I klasy gimnazjum - Julisław Łukomski (Studia Ecologiae et Bioethicae)
The article includes characteritc of additional materials for catechists and teachers, especially ecological examination of conscience and analysis of the following issues: revealed law and natural law, ecological balance, rule of general destiny of goods, celebration in connection with ecology, ecological intuitions in saints’ opinions and attitiudes, histories of Christian ecological intuitions.